Social Vulnerability, Mental Health, Education and Solidarity in Brazil in Times of COVID-19: Bioethical Reflections (Revista Iberoamericana de Bioética, 2023)
The COVID-19 global health crisis has affected the quality of life and mental health of the Brazilian population. In this context, the bioethical debate must address the need for urgently implementing public policies to support the socially excluded. This paper draws attention to factors that impact the mental health of the Brazilian population, such as social inequality, marginalization, exclusion and extreme poverty, all of which call for supportive ethical mechanisms to protect the most socially vulnerable members of society. We carried out a comprehensive review of the literature which draws on Article 14 of the Universal Declaration on Bioethics and Human Rights, focusing on the lack of freedom of the “Wretched of the Earth”. There is an evident need for a partnership capable of mobilizing a truly liberating educational project to transform mental health and ensure dignity for everyone. The aim would be to build bioethics comprising intervention, plurality and solidarity, capable of confronting social divisions that give rise to multiple negative outcomes for the oppressed of this world, jeopardizing the full development of their skills, capabilities and potential.
Keywords: mental health; education; bioethics; solidarity; COVID-19; social vulnerability